Learning Outcomes Improvement in Animal’s Life Cycle Material (Theme 6 Sub-theme 2) Through Card Sort Strategy Implementation toward Fourth Grade Students of MI Tarbiyatul Islamiyah Panjunan Sidoarjo - Nurrohmah, Revida Wahyu Putri (Indonesian Journal of Science Learning (IJSL), 2021)
This research was conducted due to the low learning outcomes of fourth-grade students of MI Tarbiyatul Islamiyah Panjunan Sidoarjo in the animal’s life cycle materials (Theme 6 Sub-theme 2). It was proved by the learning outcomes of students were still under minimum completeness criteria due to the difficulty of distinguishing the animal’s life cycle as complete metamorphosis, incomplete metamorphosis, or ametamorphosis. The minimum completeness criteria are only 40% (not good). Therefore, the effort conducted by researchers in improving learning outcomes is through the card sort strategy. The purpose of this research were; 1) describe the implementation of a card sort strategy toward fourth-grade students MI Tarbiyatul Islamiyah Panjunan Sidoarjo in animal’s life cycle material, 2) describe the increase of students learning outcomes in animal’s life cycle material after implementing the card sort strategy. This study used Classroom Action Research (CAR) with Kurt Lewin’s model in which there are 4 stages namely planning, observing, acting, and reflecting. Data collection techniques used were interviews, documentation, observation, and test. The subject of this research was 30 students of fourth grade MI Tarbiyatul Islamiyah Panjunan Sidoarjo. The results showed that; 1) The implementation of card sort strategy has been done well, it can be seen from the increase of teacher and student’s activity percentage; 2) the result of students learning outcomes has increased significantly which can be seen from student’s completeness percentage to 93%. Thus, it can be said that this research has been successful.